Immunofluorescence localization of levopimaradiene/abietadiene synthase in methyl jasmonate treated stems of Sitka spruce (Picea sitchensis) shows activation of diterpenoid biosynthesis in cortical and developing traumatic resin ducts - Zulak, Katherine; Dullat, H.; Keeling, C.; Lippert, D.; Bohlmann, J. (Pergamon, 2010)
Conifers produce terpenoid-rich oleoresin in specialized resin ducts as a main line of defence against pests and pathogens. In spruce species (Picea spp.), axial resin ducts are either present constitutively in the cortex tissue (cortical resin ducts, CRDs) or are formed de novo as traumatic resin ducts (TRDs) in the cambial zone upon attack by insects, fungi or treatment with methyl jasmonate (MeJA). Using immunofluorescence localization we tested if previously formed CRDs respond to MeJA treatment with increased capacity for diterpenoid biosynthesis. We also tested the dynamics of diterpene synthase localization in the cambial zone. Immunofluorescence localization was performed using an antibody against a diterpene synthase, levopimaradiene/abietadiene synthase (LAS), in stem cross-sections of untreated and 0.1% MeJA-treated 4-year old Sitka spruce (P. sitchensis) trees. No fluorescence signal was observed in untreated stem cross-sections; however, signal was present 2 days after treatment with MeJA exclusively in the epithelial cells of CRDs. Fluorescence steadily increased in the CRD epithelial cells 4 and 8 days after treatment. At 8 days, additional fluorescence was observed in developing epithelial cells of traumatic resin ducts TRDs in the cambial zone. These results confirm that resin duct epithelial cells are the main site of diterpene biosynthesis in Sitka spruce, diterpenoid biosynthesis is induced in CRD epithelial cells early upon treatment with MeJA, and immature developing TRD epithelial cells produce diterpene synthase enzyme. Overall, the results of this work improve our understanding of spatial and temporal patterns of induced diterpene resin acid biosynthesis in conifers. © 2010 Elsevier Ltd. All rights reserved.